(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Background: Severe chronic kidney disease requires renal replacement therapy in shape of Dialysis or Transplant. An adequately treated Hemodialysis (HD) patient is physically active, well nourished, not anemic, and not hypertensive with a maintained quality of life and life expectancy that is not inferior to that of healthy subjects. Worldwide the minimum standards of adequate HD are thrice weekly dialysis; single pool Kt/V (spKt/V) of 1.2 per dialysis and Urea reduction ratio (URR) of 65%. Objective: The objective of the study is to determine the frequency of adequacy of dialysis among patients on thrice weekly dialysis in a tertiary care hospital. Methodology: A descriptive case series study was conducted in dialysis center of Sir Ganga Ram Hospital for Six month period on Sample size of 72 patients who were receiving thrice weekly hemodialysis. URR and sKt/V were measured as markers of adequacy of dialysis along with other variables like Hemoglobin, Serum Calcium and Serum Phosphorus. Results: Regarding age distribution, majority of the patients 24 (32.0%) were between 41-50 years of age and minimum patients were 31-40 years old. Mean age was 48.60±12.87 years. Out of 72 patients, 46 (31.3%) were male while remaining 26 patients (38.7%) were female. Only 41.3% were receiving adequate dialysis in terms of Kt/V and URR. Target of adequate Hemoglobin levels were achieved in 46.7%. Serum calcium and Serum phosphorus were maintained by 50.7% and 61.3% of patients respectively within recommended range. Conclusion: Our study shows that majority of patients of ESRD undergoing regular thrice weekly maintenance hemodialysis are unable to attain the recommended adequacy of dialysis in terms of variables like URR, Kt/V and hemoglobin.